Anti-tumor Activity of Curcumin against Androgen-independent Prostate Cancer Cells via Inhibition of NF-κB and AP-1 Pathway in vitro - 刘双林 王志华 胡志全 曾星 李有元 苏耀武 章传华 叶章群 (Journal of Huazhong University of Science and Technology. Medical sciences, 2011)
The anti-tumor activity of curcumin against androgen-independent prostate cancer cells in vitro and the possible mechanism were investigated.After curcumin treatment,the effect of curcumin on the proliferation of prostate cancer PC-3 cells was assessed by CFSE staining.Flow cytometery（FCM） was performed to analyze the cell cycle and the induction of apoptosis of tumor cells.A luciferase reporter gene assay was used to determine the effects of curcumin on the activities of intracellular NF-κB and AP-1 signaling pathways.The results showed curcumin could effectively inhibit the proliferation of PC-3 cells in vitro（P0.05）.Cells were arrested at G2/M phase.After curcumin treatment,the percentage of apoptotic cells was significantly higher than in control group（P0.05）.The results of the luciferase assay revealed that curcumin selectively inhibited the activities of the NF-κB and AP-1 signaling pathways in PC-3 cells significantly.It was suggested that curcumin could exert anti-tumor activity against androgen-independent prostate cancer cells in vitro by inhibiting cellular proliferation and inducing apoptosis,which was probably contributed to the inhibition of transcription factors NF-κB and AP-1.